A Comprehensive Phylogenetic Analysis of the MAP4K Family in the Green Lineage - Pan, Lixia; Fonseca De Lima, Cassio Flavio; Vu, Lam Dai; De Smet, Ive (Frontiers in Plant Science, 2021)
Kinase-mediated phosphorylation impacts every basic cellular process. While MITOGEN-ACTIVATED PROTEIN KINASE KINASE KINASE KINASEs (MAP4Ks) are evolutionarily conserved, there is no comprehensive overview of the MAP4K family in the green lineage (Viridiplantae). Here, we identify putative MAP4K members from representative species of the two core groups in the green lineage, Chlorophyta –a diverse group of green algae – and Streptophyta – mostly freshwater green algae and land plants. From that, we infer the evolutionary relationships of MAP4K proteins through a phylogenetic reconstruction. We furthermore provide a classification in three distinct subclades for the MAP4Ks in the green lineage.